THE EXISTENCE AND CONTINUITY OF MADRASAH DINIYAH AWALIYAH (MDA) IN THE MIDST OF POPULARITY INTEGRATED ISLAMIC SCHOOLS - Dani, Rahmad; Mahariah, Mahariah (JURNAL PENDIDIKAN GLASSER, 2024)
The popularity of integrated Islamic schools has resulted in the dim existence of MDA and considering it as an educational development, of course, it has a positive impact and a negative impact, especially it can make the purpose and orientation of Islamic education may not be achieved. This study aims to determine the existence and continuity of Madrasah Diniyah Awaliyah (MDA) in the midst of the popularity of integrated Islamic schools today from a socio-economic perspective and an educational perspective. This research uses a qualitative method with a literature and field study approach. With collection techniques namely interviews, observation, and documentation. This research was conducted at SDIT Hikmatul Fadhillah, SDIT An-Nizam Medan, and MDA Al-Ikhlas. The results of this study indicate that from a socio-economic perspective, those who attend MDA are lower economic families while those who attend SDIT are upper economic families. Then MDA tends to classical religious learning, this must keep up with the times and technology and increase the creativity of MDA, while the existence of SDIT has adapted to technological advances. This research is expected to contribute to government managers as reference material in making educational policies and improvements to the implementation of education.